Cambodia: Subprime Degrees? - Ford, David (International Higher Education, 2013)
The Cambodian economy has achieved a healthy average growth rate of about 7 percent, over the past decade. Higher education has expanded more than tenfold, in the same period, and now includes 91 institutions (68 universities and 23 institutes or schools) of which 59 percent are private institutions, and almost 200,000 students. Access has improved greatly, as many new institutions and branch campuses of existing institutions have opened in provincial centers.